Doing good by stealth, whilst flirting with racism some contradictory dynamics of British multiculturalism - Husband, Charles (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This article addresses the paradoxical juxtaposition of a Labour Government pursuing progressive pluralist multicultural policies whislt simultaneously maintaining a vehement anti-asylum seeker border policy. The argument locates both of these processes in the historically formed political repertoire that informs British multiculturalism. In particular, it examines the role of the discourse of tolerance in British life and its awkward relationship to a rights based model of managing ethnic diversity.
Keywords: asylum seeking; politics of difference; transcultural health; tolerance